Development of a Self-Healing Strategy to Enhance the Overloading Resilience of Islanded Microgrids - Pashajavid, Ehsan; Shahnia, Farhad; Ghosh, Arindam (2017)
This paper proposes a self-healing strategy for two neighboring islanded microgrids (MGs) that are connected together through a normally open interconnecting static switch (ISS). Each MG is expected to support the other during power deficiencies, which is facilitated by the developed self-healing agent. This agent operates based on either a centralized approach, when data communication system is available, or a decentralized approach, when data communication system does not exist or is temporarily unavailable. The necessity and possibility of the MGs interconnection or isolation is determined based on instantaneous power generation of the distributed energy resources in both MGs (in the centralized approach) and local frequency measurements at either side of ISS (in the decentralized approach). The dynamic performance of the MGs with the proposed strategies is evaluated by PSCAD simulation studies. Furthermore, the stability of the system of coupled MGs is investigated through small-signal stability and modal analyses in MATLAB.